2020
DOI: 10.2196/15593
|View full text |Cite
|
Sign up to set email alerts
|

Testing Consultation Recordings in a Clinical Setting With the SecondEars Smartphone App: Mixed Methods Implementation Study

Abstract: Background Health care systems are increasingly looking to mobile device technologies (mobile health) to improve patient experience and health outcomes. SecondEars is a smartphone app designed to allow patients to audio-record medical consultations to improve recall, understanding, and health care self-management. Novel health interventions such as SecondEars often fail to be implemented post pilot-testing owing to inadequate user experience (UX) assessment, a key component of a comprehensive imple… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…One potential solution to ensure equity while addressing clinician concerns over misuse of recordings and lack of quality control is for health care institutions to facilitate recordings through their own health care systems that could be provided to all patients. Lipson‐Smith and colleagues at Peter MacCallum Cancer Centre in Australia have developed and piloted an audio recording phone app, drawing on input from multiple stakeholders, that patients are encouraged to use for cancer consultations 28,29 . Such a solution is patient‐centered, but hospital‐endorsed to ensure both privacy and safety of patient medical information and legal protection for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…One potential solution to ensure equity while addressing clinician concerns over misuse of recordings and lack of quality control is for health care institutions to facilitate recordings through their own health care systems that could be provided to all patients. Lipson‐Smith and colleagues at Peter MacCallum Cancer Centre in Australia have developed and piloted an audio recording phone app, drawing on input from multiple stakeholders, that patients are encouraged to use for cancer consultations 28,29 . Such a solution is patient‐centered, but hospital‐endorsed to ensure both privacy and safety of patient medical information and legal protection for clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In the US, a similar survey found that far fewer respondents recorded covertly (2.7%); 8 possibly because some health services routinely provided permission for recording. Currently, the proportion of Australian patients who record covertly is unknown; anecdotally, however, clinicians report that it is occurring 16 . Covert recording has been described as a topic of “significant legal ambiguity” 17 .…”
Section: Covert Recordings By Patientsmentioning
confidence: 99%
“…Sharing recordings with family can facilitate support and understanding. Clinicians likewise recognise recordings’ benefits for patients and for improving the quality and efficiency of their care 6 …”
mentioning
confidence: 99%
See 2 more Smart Citations